Antimicrobial activity of different endodontic sealers: An in vitro evaluation - Saha S; Samadi F; Jaiswal J; Ghoshal U (Wolters Kluwer Medknow Publications, 2010)
Background: Microbes are considered as the primary etiological agents in endodontic diseases. The ways of reducing these agents are root canal debridement, antimicrobial irrigants, and antibacterial filling materials. But the complexity of the pulp canal system presents a problem for chemomechanical preparation. One of the factors determining the success of endodontic treatment is the sealing material with a potent bactericidal effect. Aim: The aim of the present study was to assess the antimicrobial activity of endodontic sealers of different bases - in vitro. Materials and Method: The antimicrobial activity of three root canal sealers (endomethasone, AH 26, and apexit) was evaluated against seven strains of bacteria at various time intervals using the agar diffusion test. The freshly mixed sealers were placed in prepared wells of agar plates inoculated with the test microorganisms. The plates were incubated for 24, 48, 72 hours, and 7 and 15 days. The mean zones of inhibition were measured. Statistical Analysis: All statistical analysis was performed using the SPSS 13 statistical software version. The analysis of variance (ANOVA), post-hoc Bonferroni test, and paired t test were performed to reveal the statistical significance. Results: Statistically significant zones of bacterial growth inhibition were observed in descending order of antimicrobial activity: endomethasone, AH 26, and apexit. Conclusion: Zinc oxide eugenol based root canal sealer produced largest inhibitory zones followed in decreasing order by epoxy resin based sealer and least by calcium hydroxide based root canal sealer.